Industrial heritage in Teruel: An example of rural decline - del Romero Renau, Luis; Valera Lozano, Antonio; La Roca Cervigón, Neus (Geographicalia, 2018)
The aim of this paper is the analysis of the scattered industrial heritage in Teruel that meets the following criteria: located out of an urban center, not totally abandoned and other criteria. Multiple data have been explored: historic cartography; publications, databases (archives, SIPCA, etc.); social media contacts and some interviews. With the information obtained, a GIS analysis has been carried out. In conclusion, thenumber of industries abandoned or destroyed is huge in absolute numbers and comparing it to remaining industrial sites. The work expands and updates part of the SIPCA heritage information system, and reflects on the situation of abandonment of the important heritage that make mills, mines and factories in this territory. Tools of protection and awareness of a unique and unrepeatable heritage are lacking.
Keywords: Industrial heritage, province of Teruel, rural decline